Знак "Z" в образотворчій традиції населення доби пізньої бронзи - Отрощенко, В.В. (Археологія, 2023)
Посилений інтерес до знаку «Z», викликаний подіями російсько-української війни (2014—2023 рр.),
потребує ретельного аналізу його символіки та
семантики. Матеріали для нього походять із
пам’яток ІІ тис. до н. е., пов’язаних із культурами
індоіранських скотарів на теренах Східної Європи
та Західної Азії. Помічено, що перехрещені «зети»
утворюють свастики. Комбінації таких знаків дають часом несподіваний ефект. The increased interest in the sign “Z”, caused by the events of the active phase of the Russian-Ukrainian war (2014—2023), requires
a more thorough analysis of its symbolism and semantics. At first glance, they are quite transparent. The count O. Bobrynskyi,
an outstanding researcher of archaeology of Ukraine and head of the Imperial Archaeological Commission, convincingly
proved the bird symbolism of the sign “Z” and its genetic connection with the swastika, based on materials from excavations in
Europe. In the context of the count’s logical reasoning regarding the meaningful load of these signs, a reference to the thesis of
the German researcher Von der Schtengen regarding the swastika as a symbol of the Indo-Germanic race sounded prophetically.
Some 30 years had remained before the practical implementation of this thesis by Nazi Germany. For the rushist Russian Federation
to choose the symbol of provocation of the World War III, the genetic component of the swastika, namely the sign “Z”,
was enough.
In addition, the topic of the article is the functioning of the named signs during the first half — the middle of the II millennium
BC, when the Indo-Aryan tribes entered the world history with the above-mentioned symbols. At a distance of three or four
thousand years, these events are seen by us as the “heroic age” of war chariots, although they do not become any less bloody. The
study convinces that “zetas” and “swastikas” are mobile signs, capable of transformations and reincarnations in the context of
the lines of other signs of that era, being components of the sign system of the tribes of the log community. The previously noted
division of swastikas into right- and left-sided ones is interpreted, in particular, by gender, as “male” and “female”, respectively.
So, within the mentioned sign system, a conflict between signs of different orientations is noticed, which can be considered within
the limits of binary opposition, dialectical unity and the struggle of opposites, where the struggle is relative, and the unity is
universal. This division can also be assumed for right- and left-sided zetas, as genetic components of swastikas.